Improving compliance of the EU Cohesion Policy via prevention measures? The case of the Polish Operational Programme ‘Technical Assistance’ 2014–2020 - Walczyk , Julia; Dotti, Nicola Francesco (European Spatial Research and Policy, 2021)
The EU Cohesion Policy was observed to be marked by financial compliance problems due to a relatively high level of irregularities. This problem brings into question the issue of how to prevent such infringements of the rules applicable to EU expenditure. Against this backdrop, this article investigates how Poland worked to prevent irregularities during the 2014–2020 programming period. Specifically, the focus is on whether prevention measures enhanced Poland’s financial compliance performance. For this purpose, a novel model of ‘non-compliance financial rate’ (NCFR) is proposed and triangulated with qualitative findings from semi-structured interviews and documentary analysis, which has shown encouraging results that might be relevant also for other Member States.